Monitoring Iraq's dual-use capabilities: An interview with Gabriele Kraatz-Wadsack. (4th July 2021) - Lentzos, Filippa
ABSTRACT: In this interview, a former biological weapons chief inspector for UNSCOM describes the importance of biological monitoring in Iraq, its challenges, and its successes.